Prey and habitat characteristics contribute to hotspots of distribution for an endangered coastal dolphin - Brough, Tom E.; Rayment, William J.; Slooten, Liz; Dawson, Steve (Frontiers in Marine Science, 2023)
Introduction Understanding the characteristics of hotspots of species distribution provides opportunities for habitat-based management; a vital and often missing component in the conservation of mobile marine species. Correlates of species distribution derived from species distribution models (SDMs) are assumed to represent the characteristics of important habitat, which often include physical and biological (i.e., prey) components. In this study, we integrate surveys of Hector’s dolphin (Cephalorhynchus hectori) with in-situ data on environmental characteristics and prey to identify the statistical correlates of distribution and to assess ‘what makes hotspots unique’. Methods Between 2014 and 2017, ca. 300 surveys were carried out at hotspots and areas not routinely used by dolphins at Banks Peninsula on the east coast of New Zealand’s South Island. A broad range of prey and environmental variables were explored as drivers of dolphin distribution using generalized additive models, and principal component analysis was employed to determine a key environmental signature for hotspots. Results The relative abundance of dolphins was strongly correlated with prey abundance and a range of environmental variables representing habitat type and oceanographic conditions. The combination of high prey abundance and sandy, shallow, high current and low turbidity habitat was strongly represented at hotspots. Discussion These characteristics are also likely attributes of habitat with high ecological value generally, being related to high biodiversity, productivity, naturalness and ecosystem function. This study showcases the importance of targeted investigations into the characteristics of species hotspots to better guide the management of important areas for the conservation of both species and ecosystems.